2020
DOI: 10.1111/gtc.12748
|View full text |Cite
|
Sign up to set email alerts
|

MLH1‐mediated recruitment of FAN1 to chromatin for the induction of apoptosis triggered by O6‐methylguanine

Abstract: O6‐Methylguanines (O6‐meG), which are produced in DNA by the action of alkylating agents, are mutagenic and cytotoxic, and induce apoptosis in a mismatch repair (MMR) protein‐dependent manner. To understand the molecular mechanism of O6‐meG‐induced apoptosis, we performed functional analyses of FANCD2 and FANCI‐associated nuclease 1 (FAN1), which was identified as an interacting partner of MLH1. Immunoprecipitation analyses showed that FAN1 interacted with both MLH1 and MSH2 after treatment with N‐methyl‐N‐nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The FAN1-MLH1 interaction may play a structural role, which potentially determines DNA cleavage specificity. Finally, it has been proposed that FAN1 interacts with MSH2 following treatment with alkylating agents [43], but this finding has not been independently confirmed and direct interaction of FAN1 with MSH2 (or its partners MSH3 or MSH6) was not demonstrated.…”
Section: Fan1 Protein Structure Domains and Protein Interactionsmentioning
confidence: 98%
See 3 more Smart Citations
“…The FAN1-MLH1 interaction may play a structural role, which potentially determines DNA cleavage specificity. Finally, it has been proposed that FAN1 interacts with MSH2 following treatment with alkylating agents [43], but this finding has not been independently confirmed and direct interaction of FAN1 with MSH2 (or its partners MSH3 or MSH6) was not demonstrated.…”
Section: Fan1 Protein Structure Domains and Protein Interactionsmentioning
confidence: 98%
“…Thus, functional MMR is essential to ensure the fidelity of DNA replication but also for genome integrity in non-mitotic cells. Cells treated with the alkylating agent, N-methyl Nnitrosourea (MNU), accumulate FAN1 nuclear foci in an MLH1-dependent manner [43]. Authors of this study propose that FAN1 exo-nuclease generates ssDNA to activate a DNA damage response, ultimately triggering apoptosis [43].…”
Section: Fan1 and Dna Repair-related Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest a generalized protective role for FAN1 in repeat expansion, although the mechanistic bases remain unclear. Nevertheless, a physical interaction between FAN1 and MLH1 has been documented, and this interaction has been suggested to play a role in the DNA damage response [108,[207][208][209]. Also, it has been suggested that FAN1 binding to CAG extrusions may block access of MutS␤ such structures, thus preventing CAG expansion [158,210].…”
Section: Mechanisms Of Mmr-mediated Cag Repeat Expansionmentioning
confidence: 99%